Thinking falls - taking action: development of a guide to action for falls prevention tool (GtA) - Robertson, Kate; Logan, Phillipa A.; Conroy, Simon P.; Dodds, Verity; Gordon, Adam L.; Challands, Linda; Smith, Sue; Humpage, Sally; Burn, Ann (Mark Allen Healthcare, 2010)
Clinical guidelines and research papers help clinicians measure and understand the risk of falling in their older clients but very few provide the assessor with recommendations as to which interventions they can use to reduce the risk of a fall.